A new semi-empirical kinetic method for the determination of ion exchange constants for the counterions of cationic micelles - Khan, Mohammad Niyaz (Elsevier, 2010)
A new method, based upon semi-empirical kinetic approach, for the determination of ion exchange constant for ion exchange processes occurring between counterions at the cationic micellar surface is described in this review article. Basically, the method involves a reaction kinetic probe which gives observed pseudo-first-order rate constants (k(obs)) for a nucleophilic substitution reaction between the nonionic and anionic reactants (R and S) in the presence of a constant concentration of both reactants as well as cationic micelles and varying concentrations of an inert inorganic or organic salt (MX). The observed data (k(obs), versus [MX]) fit satisfactorily (in terms of residual errors) to an empirical equation which could be derived from an equation explaining the mechanism of the reaction of the kinetic probe in terms of pseudophase micellar (PM) model coupled with another empirical equation. This (another) empirical equation explains the effect of [MX] on cationic micellar binding constant (K(S)) of the anionic reactant (say S) and gives an empirical constant, K(X/S). The magnitude of K(X/S) is the measure of the ability of X(-) to expel S(-) from a cationic micellar pseudophase to the bulk aqueous phase through ion exchange X(-)/S(-). The values of K(X/S) and K(Y/S) (where Y(-) is another inert counterion) give the ion exchange constant, K(X)(Y) (=K(X)/K(Y) where K(X) and K(Y) represent cationic micellar binding constants of X(-) and Y(-), respectively). The suitability of this method is demonstrated by the use of three different reaction kinetic probes and various MX.